1998
DOI: 10.1002/1529-0131(199811)41:11<2068::aid-art23>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Exercise protects against articular cartilage degeneration in the hamster

Abstract: Objective. It has been reported that osteoarthritis can occur in hamsters. The present study was undertaken to determine the effects of exercise on the composition of articular cartilage and synovial fluid and on the development of cartilage degeneration in these animals.Methods. Young (2.5-month-old) group-housed hamsters were compared with 5.5-month-old hamsters that had undergone 3 months of daily wheel running exercise (6-12 km/day) or 3 months of sedentary, individually housed living. The condition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
2
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 37 publications
(16 reference statements)
6
64
2
2
Order By: Relevance
“…Hydroxyproline analysis. The hydroxyproline content of cartilage extracts was determined according to the HPLC method of Otterness et al (25), with minor modifications. Briefly, after acid hydrolysates were derivatized with 9-fluorenylmethoxycarbonyl, they were loaded directly into a 100-l injection loop in 50% solvent B (acetonitrile/methanol/ water; 40%/40%/20% [v/v/v]) at a flow rate of 1.5 ml/minute.…”
Section: Study Design the Institutional Animal Care And Usementioning
confidence: 99%
“…Hydroxyproline analysis. The hydroxyproline content of cartilage extracts was determined according to the HPLC method of Otterness et al (25), with minor modifications. Briefly, after acid hydrolysates were derivatized with 9-fluorenylmethoxycarbonyl, they were loaded directly into a 100-l injection loop in 50% solvent B (acetonitrile/methanol/ water; 40%/40%/20% [v/v/v]) at a flow rate of 1.5 ml/minute.…”
Section: Study Design the Institutional Animal Care And Usementioning
confidence: 99%
“…Because dynamic loading of cartilage has a trophic effect on cartilage (1), frequent dynamic loading, especially in a healthy range, would cause cartilage to become thicker (2), and if cartilage thickness prevents disease, OA might occur less frequently in individuals engaging in regular activity. In most animal studies, weight-bearing exercise has been shown to protect against the development of OA (3,4), but in one strain of centrally stimulated animals that run almost constantly, there is a high rate of cartilage loss versus control animals (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Articular rigidity and a decreased range of motion, due to lower weight bearing caused by nerve injury, may be responsible for thickening of the synovial membrane 23 , leading to a lower level of proteoglycans 45 , which interferes with the production of synovial fluid and consequently reduces the supply of nutrients to the cartilage 23,35 . According to Kojima, Hoso, Watanabe, Matsuzaki, Hibino, Sasaki 46 , these changes may be related to the presence of flocculation, corrosion and cracks in the articular cartilage.…”
Section: Discussionmentioning
confidence: 99%